2008
DOI: 10.1111/j.1365-2583.2008.00803.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and RNAi‐mediated functional characterization of MaLac2 of the pine sawyer, Monochamus alternatus

Abstract: Laccase, a member of a group of proteins collectively known as multicopper oxidases, is hypothesized to play an important role in insect cuticle sclerotization by oxidizing catechols in the cuticle to their corresponding quinones, which then catalyze protein cross-linking reactions. Laccase 2 has been proved as the gene required for beetle cuticle tanning through RNA interference (RNAi) experiments on red flour beetle Tribolium castaneum. The pine sawyer beetle, Monochamus alternatus (Coleoptero: Cerambycidae)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 24 publications
(39 reference statements)
3
52
1
1
Order By: Relevance
“…The activity of this enzyme was studied in the cuticle of dipteran (Yamazaki, 1969; Barret and Andersen, 1981;Barrett, 1987a,b;Binnington and Barrett, 1988;Sugumaran et al, 1992;Charalambidis et al, 1994) and lepidopteran species (Yamazaki, 1972;Thomas et al, 1989), and in some of them the temporal changes in the activity seemed to be linked to cuticle sclerotization. More recently, cDNAs for one or for the two laccase genes (lac1 and lac2) found in insect genomes were characterized in species of Diptera and Lepidoptera (Dittmer et al, 2004;Gorman et al, 2008;Pan et al, 2009;Yatsu and Asano, 2009), and also in two species of Coleoptera (Arakane et al, 2005;Niu et al, 2008). Additionally, the amino acid sequence of laccase2 from the cuticle of Manduca sexta was experimentally determined by expressing and purifying full-length and recombinant forms of the protein (Dittmer et al, 2009), thus confirming identity predicted from the corresponding cDNA sequence (Dittmer et al, 2004).…”
Section: Introductionmentioning
confidence: 78%
“…The activity of this enzyme was studied in the cuticle of dipteran (Yamazaki, 1969; Barret and Andersen, 1981;Barrett, 1987a,b;Binnington and Barrett, 1988;Sugumaran et al, 1992;Charalambidis et al, 1994) and lepidopteran species (Yamazaki, 1972;Thomas et al, 1989), and in some of them the temporal changes in the activity seemed to be linked to cuticle sclerotization. More recently, cDNAs for one or for the two laccase genes (lac1 and lac2) found in insect genomes were characterized in species of Diptera and Lepidoptera (Dittmer et al, 2004;Gorman et al, 2008;Pan et al, 2009;Yatsu and Asano, 2009), and also in two species of Coleoptera (Arakane et al, 2005;Niu et al, 2008). Additionally, the amino acid sequence of laccase2 from the cuticle of Manduca sexta was experimentally determined by expressing and purifying full-length and recombinant forms of the protein (Dittmer et al, 2009), thus confirming identity predicted from the corresponding cDNA sequence (Dittmer et al, 2004).…”
Section: Introductionmentioning
confidence: 78%
“…Expression of laccase genes in M. sexta depends on both the developmental stage of the animal and the type of tissue (Dittmer et al, 2004). Studies using RNA interference showed that the product of the laccase2 gene is essential for cuticular sclerotization in the beetles Tribolium castaneum (Arakane et al, 2005) and Monochamus alternatus (Niu et al, 2008), and not only was cuticular sclerotization prevented in the RNA interference experiments, but the thickness and structure of the procuticle were also affected. Two isoforms of laccase2, TcLac2A and TcLac2B, are present in T. castaneum, they are reported to play different but indispensable roles in cuticular sclerotization, with TcLac2A making the major contribution (Arakane et al, 2005).…”
Section: Oxidation Of Cuticular Catechols To Ortho-quinonesmentioning
confidence: 95%
“…One method used to prevent this nematode from damaging forests involves preventing its transportation by controlling M. alternatus. In the past several years, M. alternatus research has focused on the following topics: (i) the relationship between the M. alternatus larval instar stages and the effectiveness of PWN transmission (Naves et al, 2007;Zhao et al, 2007), (ii) the effect of volatiles from different pines on M. alternatus finding mating locations (Fan et al, 2007), (iii) M. alternatus feeding (Li et al, 2007) and oviposition (Fan et al, 2007), (iv) the phylogeography and genetic diversity of M. alternatus (Kawai et al, 2006a(Kawai et al, , 2006b, (iv) laccase (Niu et al, 2008), (v) α-tubulin and (vi) various pheromones (Teale et al, 2011). Very little, however, is known about the genes involved its biological processes, cellular components and molecular functions, such as the genes encoding insecticide targets and related to insecticide resistance.…”
Section: Introductionmentioning
confidence: 99%